Linguistic data science and the English passive: modelling diachronic developments and regional variation - Bohmann, Axel; Müller, Julia; Honkanen, Mirka; Neuhausen, Miriam (Bloomsbury Academic, 2025)
The choice between BE and GET as auxiliary verbs, as in “She was promoted” vs “She got promoted”, is a central, grammatical feature, yet the many proposed nuances conditioning this phenomenon have escaped large-scale empirical validation to date. This book fills this gap, using multivariate statistical analyses of several large corpora to explore different factors determining the choice of English passive auxiliary.
Literaturverzeichnis: Seiten [237]-264